Gandhian Concept of Bhagavad-Gītā: An Analysis - Beher, Naresh Kumar; Kar, Sarita (International Journal of Psychosocial Rehabilitation, 2020)
Gandhi’s spiritual thought, religious ideas, social vision and political activity are deeply influenced by Bhagavad-Gītā. He not only had an intense love for the scripture but his life as a whole took shape with the philosophy of Gītā. He acquainted with Gītā in England, and he began reading Gītā thereafter. During his imprisonment years, he understood and internalized the philosophical teachings of the text. Gandhi was inspired by Gītā, during Swaraj struggle (India self-rule), to bring a spiritual awakening in the nation through non-violence (ahimsa) and truth.Gandhi started his discourse on Gītā towards the end of February 1926 at his ashram. Even he began smearing his understanding of the teachings in his own life and started experimenting with this age-old scripture to solve the political and social problems of that time. The first part of the paper explains how Gandhi’s life and philosophy are influenced by Bhagavad-Gītā. The paper studies his autobiography, which indicates how Gītā motivates him to bring a Swaraj (India self-rule). Second part of the paper will clarify how Gandhi interpreted Gītā’s lessons to build up his philosophical concepts of non-violence (ahimsa) and Satyagraha.